2019
DOI: 10.1080/10400435.2019.1682084
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the use of smartphones and tablets among people with visual impairments: Are mainstream devices replacing the use of traditional visual aids?

Abstract: Smartphones and tablets incorporate built-in accessibility features, but little is known about their impact within the visually impaired population. This study explored the use of smartphones and tablets, the degree to which they replace traditional visual aids, and factors influencing these decisions. Data were collected through an anonymous online survey targeted toward visually impaired participants above the age of 18, whom had been using a smartphone or tablet for at least three months. Among participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 35 publications
(34 reference statements)
1
46
0
Order By: Relevance
“…An exploratory study on smartphone use among people with visual impairment shows that more than 90% of respondents used their mobile for activities such as calls, sending and receiving message, browsing the web, reading emails; 70-80% of them used smartphone for calendar functions, listening music and social media, and networking; 60 to 70% of them used for reminders and to take photos for reading with Optical Character Recognition [18]. This study also shows that 80% of participants used a smartphone for outdoor GPS navigation.…”
Section: Use Among Visually Impaired and Blindnessmentioning
confidence: 99%
See 1 more Smart Citation
“…An exploratory study on smartphone use among people with visual impairment shows that more than 90% of respondents used their mobile for activities such as calls, sending and receiving message, browsing the web, reading emails; 70-80% of them used smartphone for calendar functions, listening music and social media, and networking; 60 to 70% of them used for reminders and to take photos for reading with Optical Character Recognition [18]. This study also shows that 80% of participants used a smartphone for outdoor GPS navigation.…”
Section: Use Among Visually Impaired and Blindnessmentioning
confidence: 99%
“…In many cases, the smartphones apps can function for multipurpose tasks that facilitate independence living. Natalina et al study also highlighted that the smartphones are replacing many traditional assistive solution to a great extend in doing daily activities [18]. A few studies reported that participating in digital arenas and accessing digital technology, including smartphones, reduce loneliness feeling, improve social contact, information sharing, gaining a better interaction with friends and family [21][22][23].…”
Section: Use Among Visually Impaired and Blindnessmentioning
confidence: 99%
“… 9 10 As for more contemporary technologies (eg, head-mounted displays), cybersickness and headaches influence device use. 7 However, mainstream devices (eg, tactile tablets and smartphones) have been described as great equalisers and facilitators of device acceptance 11 ; they are perceived as ‘normal’ when used in public, and are appreciated for their modern aesthetics. 12 …”
Section: Barriers and Facilitators Of Device Use Or Abandonment In Simentioning
confidence: 99%
“…Advances in technology now enable the design of a new generation of wearable electronic sight aids 7,8 . Positive signs of successfully utilising new technological capabilities also come from everyday consumer devices being increasingly utilised by and for people with visual impairment 9,10 …”
Section: Introductionmentioning
confidence: 99%